Develop Responsive Websites with Bootstrap 3 - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2014)
"In the Develop Responsive Websites with Bootstrap 3 course, we will walk you through the popular Bootstrap HTML and CSS framework. Bootstrap helps build websites that look beautiful on mobile, tablet, and desktop browsers. Develop Responsive Websites with Bootstrap 3 covers a wide range of use cases from simple marketing websites, to web application UI's to dynamic websites using a CSS pre-processor that builds Bootstrap on the fly. In the course, you will learn about various stylized components of Bootstrap 3 including Navbars, Buttons, Panels, Images, Accordions, Modal dialog boxes and the like, while building two demonstration websites. You will also learn about the underlying architecture including the layout grid, responsive techniques, typography, and utility functions for layout, hardcopy print and screen readers. By the end of this course you will have created a beautifully designed responsive website for your portfolio. After taking the course and creating the project website, you will be able to take what you've learned and create virtually any other type of website on the web today. You will also create your own custom web application UI. Customization of Bootstrap is introduced in simple CSS overrides, expanded upon with 3rd-party Javascript functions (for high-resolution Retina images), and developed finally in the creation of your own Bootstrap template. You will also learn about CSS debugging techniques which are helpful in customizing Bootstrap with its CSS pre-processor language LESS. In the last two lessons, you will create a dynamic version of one of the demo websites with a Node.js server and on-demand compiled Bootstrap LESS. Example code is provided for each lesson."--Resource description page.
Title from resource description page (viewed December 9, 2014)
Presenter, Stone River eLearning.
Keywords: Bootstrap (Computer program); Web site development -- Computer programs; Electronic books